A Rare PTPN11 Mutation in a Patient with Juvenile Myelomonocytic Leukemia: A Case Report - Khanmohammadi, Shaghayegh; Zoghi, Samaneh; Rayzan, Elham; Shahkarami, Sepideh; Jimenez Heredia, Raul; Frohne, Alexandra; Seyedpour, Simin; Boztug, Kaan; Rezaei, Nima (Current Pharmacogenomics and Personalized Medicine, 2022)
Background: Juvenile myelomonocytic leukemia (JMML) is a rare childhood disease characterized by hepatosplenomegaly, monocytosis, anemia, increased white blood cell count, thrombocytopenia, skin infiltration, and elevated fetal hemoglobin. Mutation in specific genes, including KRAS, NRAS, PTPN11, and NF1, can lead to the development of JMML. Case Presentation: A two-year-old boy with a history of inguinal abscess at the age of 12 months and surgery due to infectious lymphadenitis was referred to the hospital. His parents also reported a history of oral candidiasis, recurrent otitis media, and lymphadenopathy in the patient. The physical examination showed splenomegaly, macular rash, lymphadenopathy in the neck region, and rashes in the inguinal region and on the hands and feet. Laboratory and flow cytometry data showed lymphocytosis, low hemoglobin, thrombocytopenia, monocytosis, eosinophilia, and a shift to the left in the peripheral blood. The bone marrow aspiration showed a cellular marrow with myeloid hyperplasia. Whole-exome sequencing revealed a rare heterozygous ENST00000351677.2:c.1508G>C, p.Gly503Ala variant in PTPN11. The patient was diagnosed with JMML but, unfortunately, passed away. Conclusion: We report a rare heterozygous mutation in the PTPN11 gene in a two-year-old boy diagnosed with JMML. This uncommon mutation should be considered in the mutational screening protocol of JMML. Management of JMML with RAS pathway targeted therapy may also have promising results and needs further investigations.
Keywords: RAS pathway